2018
DOI: 10.1016/j.bja.2018.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetic-induced myotoxicity in regional anaesthesia: a systematic review and empirical analysis

Abstract: Recent reports of local-anaesthetic (LA)-induced myotoxicity after peripheral nerve blocks have increased the interest in this less commonly known complication. Basic science evidence investigating LA-induced myotoxicity seems to demonstrate a pattern, but findings from human studies vary. This systematic review summarises the existing myotoxicity evidence and empirically examines its implications. Databases were searched for all in vitro animal and human studies evaluating LA-induced myotoxicity. Studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 129 publications
(339 reference statements)
0
51
0
Order By: Relevance
“…Myotoxicity is known to occur after local anesthetic injection, and in vitro data suggest this effect is concentration-dependent 16. Most adverse clinical effects have occurred after retrobulbar block, although rare cases of myotoxicity are reported after interscalene and trigger point injections 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myotoxicity is known to occur after local anesthetic injection, and in vitro data suggest this effect is concentration-dependent 16. Most adverse clinical effects have occurred after retrobulbar block, although rare cases of myotoxicity are reported after interscalene and trigger point injections 16.…”
Section: Discussionmentioning
confidence: 99%
“…Most adverse clinical effects have occurred after retrobulbar block, although rare cases of myotoxicity are reported after interscalene and trigger point injections 16. Increased toxicity associated with bupivacaine has been suggested as a motivation for using ropivacaine when performing ACB.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery time in human muscles ranged from 4 days to 1 year. None partial and complete recovery was observed in 61% and 38% of patients, respectively [61]. All LAs that have been studied have a similar myotoxic potential in terms of the tissue alterations produced, but they differ in the intensity of these lesions.…”
Section: Myotoxicitymentioning
confidence: 92%
“…Recent findings in adults showed an increased risk for myotoxicity for continuous adductor canal block; hence, the risks and benefits for perineural catheter in this space should be equally and carefully balanced in children. 16 Whilst evidence is still lacking in children, studies in adults have confirmed that the SN block at the level of the adductor canal offers a similar analgesic profile to the FN block for knee surgery while preserving quadriceps strength. 17,18 Obturator nerve block…”
Section: Clinical Tipsmentioning
confidence: 99%